2022
DOI: 10.3847/1538-3881/ac6f58
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Analysis of the Rich Planetary System of the Nearby Star e Eridani: Ideal Targets for Exoplanet Imaging and Biosignature Searches

Abstract: e Eridani, the fifth-closest Sun-like star, hosts at least three planets and could possibly harbor more. However, the veracity of the planet candidates in the system and its full planetary architecture remain unknown. Here we analyze the planetary architecture of e Eridani via DYNAMITE, a method providing an integrative assessment of the system architecture (and possibly yet-undetected planets) by combining statistical, exoplanet-population-level knowledge with incomplete but specific information available on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…An albedo of 0.3 was assumed for each planet. Although the true distribution of exoplanet albedos is currently unknown, Basant et al (2022) has shown this value to be a reasonable prior based on known solar system and exoplanet constraints.…”
Section: Planetary Atmospheres and Predicted Contrast Ratiosmentioning
confidence: 99%
“…An albedo of 0.3 was assumed for each planet. Although the true distribution of exoplanet albedos is currently unknown, Basant et al (2022) has shown this value to be a reasonable prior based on known solar system and exoplanet constraints.…”
Section: Planetary Atmospheres and Predicted Contrast Ratiosmentioning
confidence: 99%